Evaluation of Carcinogenic Potential of Diuron in a Rat Mammary Two-Stage Carcinogenesis Model - Grassi, Tony Fernando [UNESP]; Rodrigues, Maria Aparecida Marchesan [UNESP]; Camargo, João Lauro Viana de [UNESP]; Barbisan, Luis Fernando [UNESP] (Sage Publications Inc, 2011)
This study aimed to evaluate the carcinogenic potential of the herbicide Diuron in a two-stage rat medium-term mammary carcinogenesis model initiated by 7,12-dimethylbenz(a)anthracene (DMBA). Female seven-week-old Sprague-Dawley (SD) rats were allocated to six groups: groups G1 to G4 received intragastrically (i.g.) a single 50 mg/kg dose of DMBA; groups G5 and G6 received single administration of canola oil (vehicle of DMBA). Groups G1 and G5 received a basal diet, and groups G2, G3, G4, and G6 were fed the basal diet with the addition of Diuron at 250, 1250, 2500, and 2500 ppm, respectively. After twenty-five weeks, the animals were euthanized and mammary tumors were histologically confirmed and quantified. Tumor samples were also processed for immunohistochemical evaluation of the expressions of proliferating cell nuclear antigen (PCNA), cleaved caspase-3, estrogen receptor-alpha (ER-alpha), p63, bcl-2, and bak. Diuron treatment did not increase the incidence or multiplicity of mammary tumors (groups G2 to G4 versus Group G1). Also, exposure to Diuron did not alter tumor growth (cell proliferation and apoptosis indexes) or immunoreactivity to ER-alpha, p63 (myoephitelial marker), or bcl-2 and bak (apoptosis regulatory proteins). These findings indicate that Diuron does not have a promoting potential on mammary carcinogenesis in female SD rats initiated with DMBA.
Keywords: pesticides; diuron; mammary carcinogenesis; Sprague-Dawley rats; toxicology